Computational fluid dynamics principles and applications - Blazek, J.
Computational Fluid Dynamics (CFD) is a design tool in engineering and also a substantial research tool in various physical sciences as well as in biology. This book provides a foundation for understanding the numerical methods employed in CFD and presents the CFD codes. It includes tools for Von Neumann stability analysis of 1-D model equations.